Arm coordination and performance level in the 400-m front crawl - Schnitzler, C.; Seifert, L.; Chollet, D. (Research Quarterly for Exercise and Sport, 2011)
The purpose of this study was to determine whether the Index of Coordination (IdC) and the propulsive phase durations can differentiate performance level during a maximal 400-m front crawl swim trial. Sixteen male swimmers constituted two groups based on performance level (G1: experts; G2: recreational). All participants swam the 400-m front crawl at maximal speed. Video analysis determined the stroke (swimming speed, stroke length, stroke rate) and coordination (IdC) parameters for every 50 m. Both stroke and coordination parameters discriminated performance level. The expert group had significantly higher values for speed and stroke length and lower values for the relative propulsive phase duration and IdC (p < .05). However, there was no significant change in coordination parameters for either group throughout the trial. This suggests that, when associated with greater stroke length, catch-up coordination can be an efficient coordination mode that reflects optimal drag/propulsion adaptation. This finding provides new insight into swimmers' adaptations in a middle-distance event.